UTIL: uma taxonomia unificada para visualização de informação - Diego Augusto de Faria Barros (2015)
Different taxonomies and classification models have been proposed to describe data visualization techniques and possible user interactions. Nonetheless, different models focus on distinct aspects and may be more appropriate according to the goal or context in which the visualization is being used. Currently, none of them are broad enough to encompass all the possible features that may be relevant, nor is there an easy way to compare them and choose the one that would be more adequate in a specific context. In this work we have performed a Systematic Literature Review and analyzed the features described in existing models. Based on this analysis we propose UTIL, a unified model that can be used to describe and compare existing models. In order to conduct a evaluation, we have chosen some consolidated works and described them using UTIL and discuss how it can make clear the differences between different models and their focuses.